EFFECTS OF SEX AND GENOTYPE ON MORPHOMETRIC TRAITS OF RABBIT (FUDMA JOURNAL OF SCIENCES, 2021)
A total of one hundred (100) matured rabbit of 4 â€“ 6 month of age comprising of New Zealand White (NZW) and Dutch (DUT) breeds were used in the study. They comprised of forty nine (49) New Zealand White, thirteen (13) males and thirty six (36) females, Fifty one (51) Dutch breed comprising of twenty one (21) males and thirty (30) females. The experiment was conducted at the Livestock Teaching and Research Farm, University of Maiduguri, Borno State. Maiduguri. The management system used was intensive system and semi intensive system.  By housing them in a cage based on breed and sex. Each rabbit is housed in a cage measuring 33cm x 38cm x 45cm and the cages were tagged for easy identification, measurement and weighing. The cages were slightly raised above the ground for cross ventilation and to facilitate cleaning.Body weight was measured with a digital weighing scale in kilograms and the body measurements were measured using tailor tape calibrated in centimeters. The data measured are body weight (BW), body length (BL), nose to shoulder length (NSL), heart girth (HG), height at withers (HW), ear length (EL), leg length (LL), tail length (TL) and height of the rabbit (HR). Results obtained showed that sex had no significant effect on all the morphometric data measured. Significant effect of genotypes on morphometric traits were observed  on NSL, HG, HW, EL and TL with their corresponding values of 10.83, 13.57, 13.37, 14.73, 10.95 in Dutch breed and corresponding values in
Keywords: Body Weight, Genotype, Morphometric, Sex and Traits